GAMBARAN KOLESTEROL TOTAL DAN DAYA TAHAN OTOT PEREMPUAN DI PUSAT KEBUGARAN - Ichsania, Nurul (Education and Talent Development Center Indonesia (ETDC Indonesia), 2025)
Cholesterol is an important metabolic indicator that can influence physical fitness, particularly muscular endurance. Regular physical activity in fitness centers plays a significant role in maintaining cholesterol levels and enhancing muscle performance. This study aimed to describe the total cholesterol level and muscular endurance among women aged 20–40 years who actively exercise at a fitness center. This research employed a descriptive design with a cross-sectional approach involving 30 purposively selected participants. Data were collected through total cholesterol measurements using a digital cholesterol test meter and muscular endurance assessments using a one-minute sit-up test. The results showed that the mean total cholesterol level was 179.63 ± 18.75 mg/dL, while the mean muscular endurance score was 43.33 ± 5.86 sit-ups per minute. Pearson correlation analysis revealed a strong negative relationship between total cholesterol and muscular endurance (r = −0.979; p < 0.001). These findings indicate that higher total cholesterol levels are associated with lower muscular endurance. The study emphasizes the importance of regular physical activity in maintaining healthy lipid profiles and improving overall physical fitness among women of productive age.